PLTS/DEMATEL-based key policy factor identification for marine fisheries management in China - Du, Yuan-Wei; Zhang, Shi-Tong (Regional studies in marine science, 2022)
China has a number of fisheries management policies aimed at curbing the decline of fisheries resources. Due to the management subject is relatively unitary, we speculate that policies are constantly influencing each other, which results in system fault. To investigate the structural correlation between policies, a hybrid method comprising the probabilistic linguistic term set (PLTS), the Dempster–Shafer evidence theory (DST), and the decision-making trial and evaluation laboratory (DEMATEL) was proposed. First, the policy factors for China’s marine fisheries management are analyzed, and the PLTS is used to obtain the original data given by experts to describe the direct influence degree between each pair of policy factors. Then, all PLTSs are transferred to the basic probability assignment functions, and they are fused by Dempster’s rule to obtain the initial direct-relation (IDR) matrix. With the IDR matrix as inputs, the DEMATEL method was employed to identify the key policy factors. The results found that the prominence degrees of the two policies of output control were the highest, indicating that output control is the core policy type that can be critically linked to the effectiveness of policy system. Finally, the corresponding suggestions were put forward.